Still Muted: The Limited Participatory Democracy of Zoom Public Meetings. Issue 4 (July 2023) - Einstein, Katherine Levine; Glick, David; Godinez Puig, Luisa; Palmer, Maxwell
Recent research has demonstrated that participants in public meetings are unrepresentative of their broader communities. Some suggest that reducing barriers to meeting attendance can improve participation, while others believe doing so will produce minimal changes. The COVID-19 pandemic shifted public meetings online, potentially reducing the time costs associated with participating. We match participants at online public meetings with administrative data to learn whether: (1) online participants are representative of their broader communities and (2) representativeness improves relative to in-person meetings. We find that participants in online forums are quite similar to those in in-person ones. They are similarly unrepresentative of residents in their broader communities and similarly overwhelmingly opposed to the construction of new housing. These results suggest important limitations to public meeting reform. Future research should continue to unpack whether reforms might prove more effective at redressing inequalities in an improved economic and public health context.